2014
DOI: 10.1002/ijc.29269
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of JQ1 and rapamycin for treatment of human osteosarcoma

Abstract: Bromodomain and extra terminal domain (BET) proteins are important epigenetic regulators facilitating the transcription of genes in chromatin areas linked to acetylated histones. JQ1, a BET protein inhibitor, has antiproliferative activity against many cancers, mainly through inhibition of c-MYC and upregulation of p21. In this research, we investigated the use of JQ1 for human osteosarcoma (OS) treatment. JQ1 significantly inhibited the proliferation and survival of OS cells inducing G1 cell cycle arrest, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 30 publications
8
87
2
Order By: Relevance
“…9 Thus, BRD4 is a key regulator of the proliferation/apoptosis balance 12,13 by modulating gene expression and plays a critical role in post-DNA damage events. 17 In cancer, BRD4 is a known trigger of the osteogenic factor Runt-related transcription factor 2 expression, 18,19 which was recently associated with PAH lung abnormalities (including proliferation and calcification), 20 and, interestingly, BRD4 inhibition by JQ1 suppressed vascular calcification/atherogenic processes in a hypercholesterolemic murine model. 15 Furthermore, in addition to promoting DNA damage, 17 atherogenic processes 15 and increased proliferation, 12,13 BRD4 is also associated with inflammation, diabetes mellitus, obesity, and metabolic abnormalities, 13 all playing a role in VRDs, and particularly in coronary artery disease (CAD).…”
Section: P Ulmonary Arterial Hypertension (Pah) Is a Vascularmentioning
confidence: 99%
“…9 Thus, BRD4 is a key regulator of the proliferation/apoptosis balance 12,13 by modulating gene expression and plays a critical role in post-DNA damage events. 17 In cancer, BRD4 is a known trigger of the osteogenic factor Runt-related transcription factor 2 expression, 18,19 which was recently associated with PAH lung abnormalities (including proliferation and calcification), 20 and, interestingly, BRD4 inhibition by JQ1 suppressed vascular calcification/atherogenic processes in a hypercholesterolemic murine model. 15 Furthermore, in addition to promoting DNA damage, 17 atherogenic processes 15 and increased proliferation, 12,13 BRD4 is also associated with inflammation, diabetes mellitus, obesity, and metabolic abnormalities, 13 all playing a role in VRDs, and particularly in coronary artery disease (CAD).…”
Section: P Ulmonary Arterial Hypertension (Pah) Is a Vascularmentioning
confidence: 99%
“…First, pharmacologic inhibition of BRD4 enhanced Palomid 529-induced 786-O cell death Inhibition of BRD4 could be a fine strategy to sensitize Palomid 529 in RCC cells. Previous studies have established synergistic to additive effects between mTORC1 inhibitors and bromodomain protein inhibition in various human cancers [52][53][54]. For example, Lee et al, reported the synergistic anti-osteosarcoma activity by the BRD4 inhibitor JQ1 and rapamycin [54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established synergistic to additive effects between mTORC1 inhibitors and bromodomain protein inhibition in various human cancers [52][53][54]. For example, Lee et al, reported the synergistic anti-osteosarcoma activity by the BRD4 inhibitor JQ1 and rapamycin [54]. Berenguer-Daize et al, reported that OTX015 (a novel BET inhibitor) and the mTORC1 inhibitor everolimus synergisticly inhibited glioblastoma cell growth [52].…”
Section: Discussionmentioning
confidence: 99%
“…To verify inhibition of BET bromodomains within the small intestine, mice were administered three doses (10 mg/kg) of BETi in 24 hours. Four hours after the last dose, villi and crypts of the small intestine were isolated and qPCR performed to examine the expression of PHF15, a gene that is downregulated upon BET bromodomain inhibition in a wide variety of cell types [16][17][18] . PHF15 expression was decreased by more than 75% in both villi and crypts of mice treated with BETi relative to control, demonstrating effective delivery of BETi throughout the small intestine (Fig.…”
Section: Resultsmentioning
confidence: 99%